Efficient annular aperture array (AAA) filter for thermophotovoltaic by sidewall lithography. (1st August 2022) - Cai, Maoqi; Chen, Zhiwen; Qiu, Keqiang; Wang, Yanan; Chen, Huoyao; Liu, Zhengkun; Liu, Ying; Hong, Yilin; Qiu, Jiawen
Abstract: Thermophotovoltaic (TPV) systems consume near infrared (NIR) filters, which are key components for high conversion efficiency. Bandpass filters employing annular aperture array (AAA) on a fused silica substrate are one of candidates for matching GaSb cells in high-temperature TPV. It is often placed independently between the emitter and cell, and thus spectral control and heat insulation are simultaneously realized. For high efficiency, the smaller the characteristic size and the larger the size is beneficial for the filter. Novel sidewall lithography based on conventional interference lithography and ion-beam etching is first proposed and used for cost-effective fabrication. An AAA filter with a 80 nm critical dimension in a 100 mm × 160 mm area has been fabricated successfully. After the annealing process at 500 °C, the peak transmittance is increased to 70% from 65%, and no deformation is observed in the structural parameters of the filter before and after annealing, and calculated results demonstrate that the spectral efficiency is about 61%.